Yet Another Public Health Threat: A Commentary and Examination of the Extensive Use of Bromazolam - Nelson J. Tiburcio (Public Health, 2025)
In this commentary, we examine the current state of the science as it pertains to the public health dangers of Bromazolam and its various illicit distribution networks, not only in North America but across the world. We also examine possible directions the substance use disorder (SUD) field may undertake to address the proliferation and abuse of this substance along with overdose prevention efforts that include the public health dangers of Bromazolam use.